10-6z=-7z

Simple and best practice solution for 10-6z=-7z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-6z=-7z equation:


Simplifying
10 + -6z = -7z

Solving
10 + -6z = -7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '7z' to each side of the equation.
10 + -6z + 7z = -7z + 7z

Combine like terms: -6z + 7z = 1z
10 + 1z = -7z + 7z

Combine like terms: -7z + 7z = 0
10 + 1z = 0

Add '-10' to each side of the equation.
10 + -10 + 1z = 0 + -10

Combine like terms: 10 + -10 = 0
0 + 1z = 0 + -10
1z = 0 + -10

Combine like terms: 0 + -10 = -10
1z = -10

Divide each side by '1'.
z = -10

Simplifying
z = -10

See similar equations:

| -20m-8=60 | | 133+55+x=180 | | 4y-2x-4x-2y= | | -4f+7=35 | | X+27+70=180 | | 5y^2-15y=25 | | 2(ax-3)=8x-b | | 2x+3+25+140=180 | | (ax-3)=8x-b | | 7e+4=5e-18 | | 5/4b=30 | | 2(x-3)+X=3(x-2) | | 4x+3+73+64=180 | | -9=(5/9)(f-32) | | 2ix-(4-5i)x=5i | | 16d-14=9+5d | | 5x-1=1-5x | | -11=a+3 | | -14y=9 | | y/-14=9 | | 4+14=9 | | 120+25+x=180 | | 4(x+y)=4y+y | | 4x-3y-6z=6 | | -16y=6 | | 40/5=-4x | | 130+20+x=180 | | -35/7=27x | | H=bf | | -35/7=4(6x) | | 8(-2x)-4x=-40 | | 69+2x=769 |

Equations solver categories